(untitled) (KYAMC Journal, 2017)
This prospective study was carried out on a total number of 58 eclamptic subjects during the period of July 2010 to June 2012 where 38 were undergone caesarean section (LUCS - Lower Uterine Caesarean Section) and 20 received conservative management. Mean (±SD) Age of the subjects who undergone Caesarean Section and conservative management (NVD) were 23.67±8.63 and 23.45±9.31 years respectively. Significant mean age difference was also present between these two groups. In 38 subjects of LUCS 34 subjects were recovered and rest 4 cases were died. Possible causes of death were due to heart failure and post partum pulmonary embolism. Among these 20 subjects who were treated conservatively 14 were recovered and 6 subjects were died. Causes of death in these groups were pulmonary embolism, Septic pneumonia, and HELLP syndrome. Significant difference was found between these two treatment options. It was observed that socio-demographic, economic status and BMI had significant effects on management outcome. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 583-586